Study of arthroscopic superior capsule reconstruction in the treatment of irreparable rotator cuff tears - Kai Sun; Yijin Li (Frontiers in Surgery, 2023)
BackgroundThe objective of this study was to investigate the clinical outcome and radiographic findings after arthroscopic superior capsule reconstruction (ASCR) with a new augmented autograft technique for irreparable rotator cuff tears.MethodsBetween 2018 and 2020, 11 patients whose shoulders had irreparable rotator cuff tears underwent ASCR using a fascia lata weaving mesh. Physical examination, radiography, and magnetic resonance imaging (MRI) were performed before surgery and the average follow-up was 20 months (18–24 months) after surgery. Clinical outcome scores were recorded.ResultsAverage clinical outcome scores improved significantly at the final follow-up, with 94.7 points scored on the American Shoulder and Elbow Surgeons scale (range, 85–100 points) and 34.5 points on the University of California, Los Angeles scale (33–35 points) (P < 0.05). Mean active elevation increased significantly from 30.1° to 150° (P < 0.05) and external rotation increased from 30° to 59.2° (P < 0.05). The acromiohumeral distance (AHD) increased from 3.9 ± 0.6 mm preoperatively to 10.1 ± 0.7 mm postoperatively (P < 0.05). No patient had graft tear or tendon retear during follow-up.ConclusionsASCR with a new augmented autograft can restore the function of the shoulder joint with irreparable rotator cuff tears. Our results suggest that this reconstruction technique can help obtain good clinical and radiographic outcomes, which can provide a reliable method for the treatment of irreparable rotator cuff tears.Level of EvidenceLevel IV, therapeutic case series.